1967
DOI: 10.1080/00207596708247208
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Physiological Influences Upon Spatial‐perceptual Processes in West Africa1 – Part I

Abstract: Inflziences culturelles e t ply siologiques

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
1
6

Year Published

1970
1970
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(82 citation statements)
references
References 5 publications
2
73
1
6
Order By: Relevance
“…Their data supported predictions that people living in industrialized or other "carpentered" environments would be most susceptible to the Miiller-Lyer (ML) and the Sander parallelogram (SP) illusions, and that people living in vast, open terrains would show a greater response to the horizontal-vertical (HV) and combined h orizontal-vertical-dichosection illusions. Other investigations tend to support the former prediction, but provide equivocal fmdings with regard to the latter (Berry, 1967;Dawson, 1967;Jahoda, 1966). However, Deregowski (1967) pointed out that the "foreshortening" hypothesis is only applicable to the HV effect and not to the dichosection (OS) effect, a contention borne out by the then-available data.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Their data supported predictions that people living in industrialized or other "carpentered" environments would be most susceptible to the Miiller-Lyer (ML) and the Sander parallelogram (SP) illusions, and that people living in vast, open terrains would show a greater response to the horizontal-vertical (HV) and combined h orizontal-vertical-dichosection illusions. Other investigations tend to support the former prediction, but provide equivocal fmdings with regard to the latter (Berry, 1967;Dawson, 1967;Jahoda, 1966). However, Deregowski (1967) pointed out that the "foreshortening" hypothesis is only applicable to the HV effect and not to the dichosection (OS) effect, a contention borne out by the then-available data.…”
mentioning
confidence: 81%
“…In order to clarify this issue, some investigations have been carried out within a single ethnic group living in an area with two distinct ecologies; this allows the comparison of ethnically and, in the main, culturally matched populations that have experienced different physical environments. Some of these studies provide at least limited support for the ecological hypothesis (Berry, 1968;Dawson, 1967), but others fail to do so (Berry, 1966;Gregor & MacPherson, 1965;Jahoda, 1966). Berry (1968) has argued that nonsignificant findings from intracultural comparisons could be explained through the confounding of developmental and ecological Variables.…”
mentioning
confidence: 99%
“…Similarly, Dawson (1967aDawson ( , 1967b found that in groups that had strict discipline (e.g., the Temne), children were more likely to develop a field dependent cognitive style as compared to groups which have more lenient childrearing practices (e.g., the Mende of Sierra Leone).…”
Section: Tightness-looseness Definedmentioning
confidence: 99%
“…Aceptar este hecho tiene importantes implicaciones para el sector educativo, además de que nos permite comprender diferencias que, como las diferencias presentes en el logro educativo de estudiantes de los dos sexos han sido constatadas desde hace mucho tiempo ya, sin encontrar explicaciones satisfactorias. En este sentido las diferencias cognitivas constatadas desde hace tiempo entre hombres y mujeres (Dawson, 1967, Kato, 1965y Okonji, 1969, entre otros), diferencias que permanecen presentes en la población colombiana (Hederich, Camargo, Guzmán y Pacheco, 1995), y que muestran una tendencia masculina hacia el polo de la IM y una tendencia femenina hacia el polo de la SM, podrían explicar los logros educativos diferenciados de los dos grupos genéricos. A este respecto, el estudio del Saber mostró logros matemáticos significativamente más altos envarones, y logros lectoescritos más altos en mujeres.…”
Section: Conclusiónunclassified